PELAKSANAAN PROGRAM PENANGGULANGAN KEMISKINAN PADA MASYARAKAT NELAYAN DAN IMPLIKASINYA TERHADAP KETAHANAN EKONOMI WILAYAH (Studi di Pantai Tanjung Pasir Kab. Tangerang Prov. Banten) - , Entis Sutisna; , Prof. Dr. H.A. Sudibyakto, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Poverty in fishing communities Tanjung Pasir Beach need to get the solution and way out of the government. The potential wealth of Indonesia's marine in particular fisheries are quite promising and provide new hope in the future. Therefore it is proper if the fisheries resources become best commodities because different types / species of fish that have high economic value of life in Indonesian waters. However, the utilization of potential resources, especially fish resources until now not been optimal. This research aimed to know and understand more deeply about the condition of living standards of poor fishermen in Tanjung Pasir Beach to identify potential resources that can be developed in Tanjung Pasir Beach, as well as to determine the poverty reduction programs can be implemented well, as expected, and right on target and may have implications on the Regional Economic Resilience of Tanjung Pasir Beach. The research method is used an interview method that gives emphasis on the nature of social reality. The research was conducted in Tanjung Pasir Beach Village. Determination of informants were calculated using field observations method. Informants in this research is the fishing community of poor households Tanjung Pasir Beach Village. The results showed that, the causes of poverty in Tanjung Pasir Beach of fishermen is a lack of capital, level of education, knowledge and skills of low fishing communities, a strong attachment between poor fisherman with the coach, the difficulty of changing patterns of economic behavior that consumptive, government attention to addressing poverty at the level Tanjung Pasir Beach of fishermen still low and there is no inherent control (waskat) toward programs that have been granted by the government so that these programs are not executed on target.